Application norms and research progress of cardiac magnetic resonance imaging in the management of MINOCA patients - ZHAO Xinxiang, ZHAO Xiaoying (Zhenduanxue lilun yu shijian, 2024)
Myocardial infarction without obstructive coronary artery (MINOCA) refers to myocardial infarction (MI) that occurs when the lumen area of coronary artery stenosis is ≤50%, accounting for 1% to 14% of the total MI. The etio-logy of MINOCA is complex and diverse, and accurate diagnosis and identification of the potential causes of MINOCA are crucial for guiding subsequent clinical management. Based on the unique advantages of myocardial tissue imaging, non-invasive cardiac magnetic resonance (CMR) examination has been widely recognized for its value in the management of MINOCA patients. CMR can be used to exclude diseases similar to MI, such as myocarditis and stress-induced cardio-myopathy, and identify the potential causes of MINOCA. It is a necessary diagnostic tool in the diagnostic process, helping to reduce overdiagnosis, misdiagnosis, and missed diagnosis of true MINOCA. Currently, it has been recommended by the American Heart Association (AHA) and the European Society of Cardiology (ESC) as an essential examination method in the MINOCA management process. In addition, compared with patients with coronary artery occlusion, MINOCA patients have a better short-term prognosis, but the risk of poor prognosis increases in long-term follow-up. It is necessary to pay more attention to the prognosis and risk stratification of MINOCA patients and management process. The traditional MI prognosis evaluation system is not entirely applicable to MINOCA patients, and CMR can provide valuable information for the prognosis evaluation of MINOCA patients. Currently, there are no standardized norms or guidelines for the application of CMR in the management of MINOCA patients in China. This article aims to review the application norms and prognostic value of CMR technology in clinical management of MINOCA, providing reference for clinical practice and enhancing understanding and management of this special MI lesion.